PENGARUH KOMUNIKASI DAN KOMPENSASI TERHADAP KINERJA DOSEN PROGRAM STUDI S1 AKUNTANSI UNIVERSITAS PAMULANG - Rizal, Anis Syamsu; Nurjaya, Nurjaya; Atmaja, Sri Nitta Crissiana Wirya (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2024)
The purpose of this research is to determine the influence of communication and compensation on the performance of lecturers in the Bachelor of Accounting Study Program at Pamulang University. The quantitative approach is the approach used in this research, with correlational research looking for the influence between independent variables and dependent variables. In this research, the population is all teaching staff or lecturers in the Bachelor of Accounting Study Program, Faculty of Economics and Business (FEB), Pamulang University, totaling 286 people, using a saturated sample. As for the questionnaires that were returned and could be processed, a total of 131 questionnaires were obtained. The research sample included 131 respondents. The instruments used in this research were the communication and compensation questionnaire and the lecturer performance questionnaire. The results of the research show that there is a significant influence of communication variables on the performance of lecturers in the Bachelor of Accounting Study Program at Pamulang University. This is because lecturers in the Bachelor of Accounting Study Program at Pamulang University carry out good communication, both with students, colleagues, and superiors. There is a significant influence of compensation variables on the performance of lecturers in the Bachelor of Accounting Study Program at Pamulang University. This is because Pamulang University provides good and appropriate compensation to lecturers in the Bachelor of Accounting Study Program at Pamulang University. There is a simultaneous influence of communication and compensation variables on the performance of lecturers in the Bachelor of Accounting Study Program at Pamulang University. This is due to the balance between the communication used by lecturers in the Bachelor of Accounting Study Program at Pamulang University and the compensation received by lecturers in the Bachelor of Accounting Study Program at Pamulang University.